Novel bioceramic-reinforced hydrogel for alveolar bone regeneration. (15th October 2016) - Iviglia, Giorgio; Cassinelli, Clara; Torre, Elisa; Baino, Francesco; Morra, Marco; Vitale-Brovarone, Chiara
Graphical abstract: Abstract: The osseointegration of dental implants and their consequent long-term success is guaranteed by the presence, in the extraction site, of healthy and sufficient alveolar bone. Bone deficiencies may be the result of extraction traumas, periodontal disease and infection. In these cases, placement of titanium implants is contraindicated until a vertical bone augmentation is obtained. This goal is achieved using bone graft materials, which should simulate extracellular matrix (ECM), in order to promote osteoblast proliferation and fill the void, maintaining the space without collapsing until the new bone is formed. In this work, we design, develop and characterize a novel, moldable chitosan-pectin hydrogel reinforced by biphasic calcium phosphate particles with size in the range of 100–300 μm. The polysaccharide nature of the hydrogel mimics the ECM of natural bone, and the ceramic particles promote high osteoblast proliferation, assessed by Scanning Electron Microscopy analysis. Swelling properties allow significant adsorption of water solution (up to 200% of solution content) so that the bone defect space can be filled by the material in an in vivo scenario. The incorporation of ceramic particles makes the material stable at different pH and increases the compressive elastic modulus, toughness and ultimate tensile strength. Furthermore, cell studies with SAOS-2 human osteoblastic cell line show high cell proliferation and adhesion already after 72 h, and the presence of ceramic particles increases the expression of alkaline phosphatase activity after 1 week. These results suggest a great potential of the developed moldable biomaterials for the regeneration of the alveolar bone. Statement of Significance: The positive fate of a surgical procedure involving the insertion of a titanium screw still depends on the quality and quantity of alveolar bone which is present in the extraction site. Available materials are basically hard scaffold materials with un-predictable behavior in different condition and difficult shaping properties. In this work we developed a novel pectin-chitosan hydrogel reinforced with ceramic particles. Polysaccharides simulate the extracellular matrix of natural bone and the extensive in vitro cells culture study allows to assess that the incorporation of the ceramic particles promote a pro-osteogenic response. Shape control, easy adaption of the extraction site, predictable behavior in different environment condition, swelling properties and an anti-inflammatory response are the significant characteristics of the developed biomaterial.